Microplastics in the digestive organs of little egret (Egretta garzetta) in Tanjung Rejo Village, Deli Serdang District, North Sumatra, Indonesia - ERNI JUMILAWATY; MAYANG ADINDA HARAHAP; MOHAMMAD BASYUNI; BEJO SLAMET (Society for Indonesian Biodiversity, 2025)
Abstract. Jumilawaty E, Harahap MA, Basyuni M, Slamet B. 2025. Microplastics in the digestive organs of little egret (Egretta garzetta) in Tanjung Rejo Village, Deli Serdang District, North Sumatra, Indonesia. Biodiversitas 26: 2460-2466. Microplastics, derived from the degradation of plastic waste measuring <5 mm, pose significant environmental risks. In aquatic ecosystems, microplastics can be inadvertently ingested by organisms, including waterbird species such as the little egret (Egretta garzetta). Microplastic ingestion may cause internal damage, digestive blockages, and exposure to toxic substances that threaten overall health and survival. This study aimed to identify the types, colors, and abundance of microplastics in the stomach and intestines of E. garzetta. Sampling was conducted purposively in Tanjung Rejo Village, North Sumatra, Indonesia, based on the presence of E. garzetta. Three individuals were captured using a trapping method, and their digestive tracts were extracted with 10% potassium hydroxide (KOH). Microplastics from the stomach and intestine samples were identified morphologically under a microscope and analyzed descriptively. The results revealed the presence of microplastic contamination in both the stomach and intestines, with synthetic fibers (e.g., nylon, polyester), fragments, and films being the predominant types detected. Fragments were the most abundant microplastic type, likely originating from household waste. A total of 48 particles were found in the stomach and 44 particles in the intestines. Black microplastics were the most prevalent (59%) in proportion, while blue microplastics were the least common (3%). The abundance of fiber as the second most prevalent type of microplastics, averaged 16 particles in the stomach and 14 particles in the intestines per individual. The findings confirmed the presence of microplastic contamination within the body of little egrets, with fibers, fragments, and films identified as the predominant types. These findings promote the need for further research and mitigation strategies to address microplastic pollution in waterbird habitats.